Hypoxemia detection and oxygen therapy practices in neonatal and pediatric wards across seven district and referral hospitals in Rwanda - Mushumbamwiza, Hyacinthe; Webster, Harriet H.; Kayitesi, Christine; Miller, Jasmine; Chizyuka, Nang’andu; Musabirema, Felix; Ngwije, Alida; Kateera, Brenda; Musafiri, Sanctus; Tuyisenge, Lisine; Graham, Hamish R.; Lam, Felix; et al. (Frontiers in Pediatrics, 2025)
BackgroundHypoxemia, characterized by low levels of oxygen in the blood, is a potentially fatal condition that is commonly found in pediatric and neonatal conditions that drive childhood mortality globally. The only treatment is the provision of medical oxygen, yet children in low-income countries frequently are not diagnosed or treated. In Rwanda, it is important to understand the extent to which pediatric and neonatal inpatients are monitored and treated for hypoxemia, in order to guide policy and clinical decision-making.MethodsThis retrospective cohort was undertaken through review of patient clinical case notes in seven hospitals in Rwanda. All patients, up to 14 years of age, admitted to neonatal or pediatric wards in these hospitals within a 3-month period were included in the study. In each facility, trained clinical data collectors used digital survey tools to capture demographic, clinical and outcome data, including pulse oximetry and oxygen use. Neonates were categorized as less than 1 month of age and under-5 s defined between 1 month and 59 months of age, and older children as 5–14 years of age. Our primary outcomes were proportion of admitted children screened with pulse oximetry, and proportion prescribed oxygen when found to be severely hypoxemic, on admission. Our secondary outcomes included hypoxemia prevalence, and other vital signs recorded on admission, oxygen prescription practices, and pulse oximetry screening practices on the day after admission and the day before discharge.ResultsA total of 3,085 neonatal and pediatric patient case notes were included in the analysis. Of these inpatients 86.3% (CI: 95% 85.0–87.4) were screened with pulse oximetry on admission. Of those screened, 18.6% (CI: 95% 17.2–20.1) were documented to have severe hypoxemia (SpO2 < 90%). Of 495 patients with documented severe hypoxemia on admission, 48.3% (CI: 95% 44.0–52.6) had an oxygen prescription recorded on admission, reaching 76.0% treated with oxygen across the course of their admission (CI: 95% 72.0–79.5).ConclusionsImprovements are required in management of hypoxemia in neonates and pediatric inpatients in Rwanda to ensure all patients are screened and those found to be hypoxemic are treated with medical oxygen.